RANCANGAN SISTEM PEMBELAJARAN DARING BERBASIS WEB - Yogasetya Suhanda; Ike Kurniati (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
The current learning process at STMIK Swadharma Jakarta is still conventional, in other words, that the teaching and learning process between students and lecturers can only be carried out on the condition that a meeting between students and lecturers occurs in the class. If the meeting between students and lecturers does not occur, automatically the learning process cannot be carried out. In addition, the process of delivering knowledge is almost completely carried out in the classroom which causes the delivery of knowledge to be late if the meeting does not occur. This situation can clearly hamper the learning process at STMIK Swadharma Jakarta so that it can result in reduced student understanding of a subject matter. The research method used is field research with data collection techniques through observation and interviews. Research results In this e_learning application have 4 actors, namely Admin / BAAK, Lecturers, Students, and Leaders. Admin is responsible for managing and inputting master data such as user data, lecturer data, student data, andcourse data. In addition, the E_learning Admin / BAAK teaching and learningprocess also have an important role, namely in the process of inputting class data, course material data, and in the reporting process. Lecturers provide course materials, assignments, UTS, UAS, and also input grades. Students can download material files provided by the lecturer, do assignments, UTS, and UAS by uploading files. Meanwhile, the leader can access reports. The reports produced include: user reports, course reports, E_learning KBM reports.